Quality of life in a phase 2 trial of short-course hyperthermic intraperitoneal chemotherapy (HIPEC) at interval debulking surgery for high tumor burden ovarian cancer - LUSTOSA,ROBERTO JOSÉ COSTA (2020)
ABSTRACT Introduction: to evaluate the effect of short-course (i.e.: 30 minutes) HIPEC on health-related quality of life (HRQoL) in our feasibility study; NCT02249013. Methods: a prespecified secondary end-point of our open-label, multicenter, single-arm, phase 2 trial on safety and efficacy was assessed using the European Organization for Research and Treatment of Cancer Quality of Life Questionnaire Core 30 (EORTC QLQ-C30, version 3.0). Patients were required to complete the HRQoL questionnaire at baseline, after HIPEC, and after the end of the treatment. Changes of HRQoL over time were assessed by median scores for each domain and analyzed by Friedman`s test at a significant two-sided level of 0.05. Results: fifteen patients with high tumor burden EOC were recruited from our public health system between February 2015 and July 2019. A baseline EORTC QLQ-C30 questionnaire and at least one follow-up questionnaire was received from all of the patients. No significant difference over time in the QLQC30 summary scores was observed (p>0.05). The transitory impairment on patients HRQoL immediately after the short-course HIPEC trended to return to baseline at the end of the multimodal treatment. Conclusions: we found no significant impairment of short-course HIPEC on patients HRQoL into the context of our comprehensive treatment protocol.